Os marcadores culturais da gastronomia afro-baiana na tradução para o espanhol em Dona Flor e seus dois maridos - Bento, Aline Kercia Sampaio Oliveira (2021)
This dissertation had as main objective the analysis of cultural markers of Afro-Bahian gastronomy belonging to Candomblé rituals, from the parallel corpus constituted by the novel Dona Flor and her two husbands, in Portuguese and in its translation into Spanish. To collate the data, the computer program WordSmith Tools 7.0 was used, especially the Wordlist and Concord tools. The research undertaken had an interdisciplinary approach supported by the theoretical-methodological assumptions of lexicography (BARBOSA, 1990); corpus linguistics (SARDINHA, 2000; 2004; DAYRELL, 2005; CAMARGO, 2007), lexicology (IZQUIERDO, 1998; BARBOSA, 1990), translation studies (BASSNETT, 2003; ARROJO, 1986, 1993, 1996; AUBERT, 1984, 1998, 1981). The research resulted in the cataloging of 54 cultural markers related to Afro-Bahian gastronomy, organized in lexicographical files, in the elaboration of a bilingual glossary and in the analysis of 23 lexias related to Candomblé rituals. The cultural markers, object of the research on screen, evidenced Jorge Amado's literary project of representing cultural and ancestral aspects that characterize Bahia, evidenced through the lexicon from the African diaspora. With regard to the analysis of the translation into Spanish, it was concluded that the translator opted for the foreignization of cultural markers related to Afro-Bahian cuisine and made use of notes and a glossary, but there are important cultural aspects that were not achieved. It is hoped that the lexicographical files, the bilingual glossary and the analysis presented in this dissertation can contribute to future translations of literary works by Jorge Amado and other writers dealing with the vocabulary of Afro-Bahian gastronomy.